Pengaruh Kompetensi, Pengalaman Kerja, Dan Komitmen Kerja Terhadap Produktivitas Karyawan Bagian Produksi CV Zaada Usaha Mulia - Yossy Nurega Dinakhandi; Sonny Subroto Maheri Laksono; Nuril Aulia Munawaroh (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research is motivated by a company operating in the convection/sewing sector. The aim of this research is to explain the influence of competence, work experience, work commitment on the productivity of production employees. This research was carried out at CV Zaada Usaha Mulia Kediri. The research method used is a quantitative method using questionnaires as data. This research uses a saturated sampling technique. The sample in this research was all 47 production employees of CV Zaada Usaha Mulia Kediri. The technique used for analysis is the IBM SPSS program version 22. The data analysis technique in this research is validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, f test. The results of this test concluded that the t test results showed that the competency variable partially had a significant positive effect on employee productivity with a significant value of 0.003 and a t value of 3.119. The work experience variable partially has a positive and insignificant effect on employee productivity with a significant value of 0.356 and a t-count value of 0.933. The work commitment variable partially has a significant positive effect on employee productivity with a significant value of 0.004 and a t value of 3.075. And the results of the f test show that the variables competency, work experience and work commitment have a significant effect on the productivity of production employees with a significant value of 0.000 and an F value of 20.909.